Peritoneal dialysis in extremely and very low-birth-weight infants. Issue 2 (March 2020) - Burgmaier, Kathrin; Hackl, Agnes; Ehren, Rasmus; Kribs, Angela; Burgmaier, Mathias; Weber, Lutz T; Oberthuer, André; Habbig, Sandra
The outcome of extremely low-birth-weight (ELBW) and very low-birth-weight (VLBW) infants has substantially improved in recent years. As acute kidney injury is frequent in these infants due to various risk factors, there is an increasing demand for renal replacement therapy in these patients. Data on that topic, however, are scarce. We review the available literature on that topic and report our experience on temporary dialysis in three extremely immature infants (two ELBW and one VLBW) with acute kidney failure. Peritoneal dialysis (PD) was performed for 19, 23, and 44 days until recovery of native renal function. At recent follow-up of 18 and 24 months, two patients are in good clinical condition with chronic kidney disease stages 1 and 4, respectively. One patient deceased at the age of 12 months due to secondary liver failure. The dialysis regimen applied in our study differed significantly from older infants with extremely short dwell times and accordingly high numbers of daily cycles. The use of rigid acute PD catheters was associated with less catheter-related complications (leakage, dislocation, and obstruction) as compared to ascites drainage catheters. In summary, PD was technically feasible and effective also in extremely immature infants, but frequent adjustments of dialysis regimens and high numbers of daily cycles posed immense efforts on both, parents and medical staff.